Kesiapan Pendidik dan Hambatan Terhadap Kecerdasan Buatan Generatif dalam Praktik Pembelajaran - Frismelly, Arinda; Rahayu, Wiwik; Sari, Fenti Amelia (Jurnal Pendidikan Teknik Elektro, 2025)
This study aims to identify educators' readiness and the obstacles they face in implementing Generative Artificial Intelligence (GenAI) in learning practices. The research focuses on aspects of digital literacy, perceived benefits, infrastructure readiness, as well as technical, pedagogical, and ethical obstacles. The method used is qualitative, employing in-depth interviews with ten lecturers from the Department of Electrical Engineering who have used GenAI for at least three months. Data was analyzed using the Miles and Huberman model, which includes data condensation, data presentation, and concluding. The results of the study indicate that educators' digital literacy regarding GenAI varies, influenced by age, teaching experience, and exposure to technology. Most educators have a positive perception of the benefits of GenAI, particularly in improving the efficiency of material preparation, enriching learning media, and supporting students' independent learning. However, technical skills such as prompt engineering and AI-based pedagogical understanding remain limited. Infrastructure readiness is relatively adequate at the individual level, but challenges related to internet connection quality, data security, and institutional policies act as barriers. Major obstacles include technical limitations, the lack of effective pedagogical strategies, and ethical concerns regarding academic integrity, information validity, and the potential decline in students' critical thinking abilities. In conclusion, the adoption of GenAI requires holistic readiness that includes improving digital literacy, strengthening pedagogical competencies, improving infrastructure, and formulating clear ethical policies. This research recommendation emphasizes the need for practice-based training, institutional